Kajian Tentang Kekuatan Kearifan Lokal Sebagai Model Pengembangan Toleransi Dan Kerukunan Kehidupan Beragama - Martinus Metboki (Pancasila Spectrum: Jurnal Multidisiplin, 2026)
This study aims to analyze the strength of local wisdom as a model for developing religious tolerance and harmony in Kuanfatu District, South Central Timor Regency. This study employed a qualitative approach using a case study method. Data were collected through in-depth interviews, observation, and documentation, and analyzed using descriptive interpretive analysis. The findings reveal that the red chicken-cutting ritual as a form of traditional oath or agreement plays an important social function in maintaining interreligious relationships. The ritual is not merely a cultural symbol but also contains values of respect for differences, religious freedom, solidarity, social responsibility, and commitment to maintaining community harmony. This local wisdom serves as social capital that strengthens kinship relations, prevents conflicts, and facilitates the intergenerational transmission of tolerance values. This study confirms that religious harmony can develop through cultural agreements rooted in community social experiences. Therefore, the local wisdom of Kuanfatu society can serve as a community-based model for strengthening tolerance in a pluralistic society.